'The Eagles are coming!': A Pneumatological Reinterpretation of the Old Germanic 'Beasts of Battle' Motif in the Works of J.R.R. Tolkien. (October 2021) - Neubauer, Łukasz
Abstract : J.R.R. Tolkien's imagination is invariably abundant in all sorts of peoples, races, and other forms of intelligent life, including those whose prototypes could be encountered in the natural world and which found their way into Tolkien's fiction with little alteration to their physical properties and only some modification of their often deep-rooted framework of cultural associations in Indo-European lore. This last group includes, amongst others, the Great Eagles of the Misty Mountains, Tolkien's 'dangerous machine', whose two principal affiliations appear to be with, on the one hand, the pre-Christian beliefs of the Germanic peoples (via the so-called beasts of battle) and, on the other, the pneumatological soteriology of the Roman Catholic Church (via the eagle as a creative recasting of the evangelical 'dove'). The present article is an attempt to demonstrate that these seemingly incompatible ingredients in fact came to be quite seamlessly unified in The Hobbit and, in particular, The Lord of the Rings, providing even more depth to the powerful Christian substratum of Tolkien's fiction.